2014
DOI: 10.1055/s-0034-1378137
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Brainstem Response in Term and Preterm Infants with Neonatal Complications: The Importance of the Sequential Evaluation

Abstract: Introduction Literature data are not conclusive as to the influence of neonatal complications in the maturational process of the auditory system observed by auditory brainstem response (ABR) in infants at term and preterm. Objectives Check the real influence of the neonatal complications in infants by the sequential auditory evaluation. Methods Historical cohort study in a tertiary referral center. A total of 114 neonates met inclusion criteria: treatment at the Universal Neonatal Hearing Screening Program of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…The reduction in latency values is related to the gradual process of myelination of the central structures and maturation of central auditory pathways, which are processes of cortical organization that are necessary for the proper development of hearing and language (1,6) . The decrease in latency had also been found in studies with another type of Auditory Evoked Potential (22,23) . In relation to gestational age and maturation of the auditory pathway, it was observed that the higher gestational age, the greater the maturation of wave P1, which was indicated by the decrease in latency of this wave (Table 2).…”
Section: Discussionsupporting
confidence: 61%
“…The reduction in latency values is related to the gradual process of myelination of the central structures and maturation of central auditory pathways, which are processes of cortical organization that are necessary for the proper development of hearing and language (1,6) . The decrease in latency had also been found in studies with another type of Auditory Evoked Potential (22,23) . In relation to gestational age and maturation of the auditory pathway, it was observed that the higher gestational age, the greater the maturation of wave P1, which was indicated by the decrease in latency of this wave (Table 2).…”
Section: Discussionsupporting
confidence: 61%
“…2 The mechanism of brain injury is thought to result from parenchymal damage and impaired cortical development. 2 In addition, Silva et al 8 recently reported that peri-/intraventricular hemorrhages influence alterations in auditory brain stem responses in preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors also emphasize that neural conduction is influenced by maturation and the diagnostic conclusion depends on this factor. 29 …”
Section: Discussionmentioning
confidence: 99%